2010
DOI: 10.1007/s10800-010-0154-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the geometry and operating temperature on the stability of Ti/IrO2–SnO2–Sb2O5 electrodes for O2 evolution

Abstract: Ternary IrO 2 -Sb 2 O 5 -SnO 2 anode has shown its superiorities over IrO 2 and many other electrocatalysts for O 2 evolution, in terms of electrochemical stability, activity and cost. The performance of IrO 2 -Sb 2 O 5 -SnO 2 anodes is affected by its electrochemical properties and operating conditions. In this paper, the electrochemical stability and activity of the Ti/IrO 2 -Sb 2 O 5 -SnO 2 anodes prepared with three different geometries were investigated under different operating conditions. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This procedure was repeated eight times. After the final coating, the electrodes were maintained at 550 o C for 1 h in order to calcinate the polymer and form the ternary oxide (IrO 2 -SnO 2 -Sb 2 O 5 ); XRD analysis confirmed at such at temperature these oxide phases are obtained [22]. The temperature did not exceed 600 o C to avoid the formation of TiO 2 that markedly reduces the electrocatalytic properties of the Ti/IrO 2 -SnO 2 -Sb 2 O 5 coating due to passivation [23].…”
Section: Methodsmentioning
confidence: 99%
“…This procedure was repeated eight times. After the final coating, the electrodes were maintained at 550 o C for 1 h in order to calcinate the polymer and form the ternary oxide (IrO 2 -SnO 2 -Sb 2 O 5 ); XRD analysis confirmed at such at temperature these oxide phases are obtained [22]. The temperature did not exceed 600 o C to avoid the formation of TiO 2 that markedly reduces the electrocatalytic properties of the Ti/IrO 2 -SnO 2 -Sb 2 O 5 coating due to passivation [23].…”
Section: Methodsmentioning
confidence: 99%
“…This result was attributed to higher adsorption of organics on the anode surface. Results like these, when combined with improved industrial success of mixed metal oxides [30] and the higher corrosion resistance and longer service life of IrO 2 -based anodes as compared to RuO 2 -based ones [31][32][33], justify the interest in the optimization of the synthesis of IrO 2 -based dimensionally stable anodes.…”
Section: Introductionmentioning
confidence: 92%
“…Initial MO solutions like those used for obtaining Fig. Alternatively, Qin et al justified the effect of temperature on the basis of the enhanced diffusion molecules towards the electrode surface [26]; moreover, temperature favors the breakage of the bonding between the organic molecule and solvated water. Generally speaking, high temperatures enhance the activity of electrocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been demonstrated that these oxidizing ions can be formed in solutions containing sulfate ions during electrolyses with Ti/IrO 2 -SnO 2 -Sb 2 O 5 electrodes. Alternatively, Qin et al justified the effect of temperature on the basis of the enhanced diffusion molecules towards the electrode surface [26]; moreover, temperature favors the breakage of the bonding between the organic molecule and solvated water. Fig.…”
Section: Resultsmentioning
confidence: 99%